Computational investigation of thermal process in radiated nanofluid modulation influenced by nanoparticles (Al2O3) and molecular (H2O) diameters - Bani-Fwaz, Mutasem Z; , Adnan; Mahmood, Zafar; Bilal, Muhammad; EI-Zahhar, Adel A; Khan, Ilyas; Niazai, Shafiullah (Journal of computational design and engineering, 2024)
The study of variety of Newtonian nanofluids subject to various physical model parameters gained much interest of engineers and scientists. Owing to their coolant and absorption characteristics, these are broadly found in chemical engineering, biomedical engineering (expansion and contraction of veins and arteries), detection of cancer cells through magnetic nanoparticles, microchips, and particularly in petroleum industry. This study focuses on investigation of nanofluid heat transfer applications inside a channel formed by expanding/contracting walls. A new heat transport model is introduced by adding the effects of nanoparticles and molecular diameters, thermal radiations, and walls permeability. Then, numerical code for the model is developed and executed to analyze the dynamics of the model from physical aspects. For expanding (${α }_1 = 1.0,2.0,3.0,4.0$) and contracting (${α }_1 = - 1.0, - 2.0, - 3.0, - 4.0$) walls, the velocity is examined maximum in the channel center. However, the fluid movement in the working domain is in reverse proportion for ${Re} = 1.0,3.0,5.0,7.0$. Further, high absorbent walls (${A}_1 = 0.1,0.3,0.5,0.7$) controlled the motion for both ${α }_1 > 0$ and ${α }_1 < 0$, respectively. The addition of thermal radiation number ${Rd} = 0.1,0.3,0.5,0.7$ played the role of catalytic parameter which imperatively increased the fluid temperature. Further, contracting walls and temperature ratio number ${θ }_r = 0.1,0.3,0.5,0.7$ reduced the temperature and this decrease is rapid in conventional fluid. Graphical Abstract Graphical Abstract